PHARMACOGNOSTICAL EVALUATION OF KATUKA (PICRORHIZA KURROA ROYLE EX BENTH.) (International Journal of Ayurveda and Pharma Research, 2018)
Now days, one of the major lacunae in the Ayurvedic system of medicine is adulteration of medicinal plant species i.e. raw drug. Drug sellers for their financial gains adulterate the raw drugs with cheap, similar looking drugs or other substances. So, it has become necessary for the Ayurvedic physicians and pharmaceuticals to identify the raw drug before its clinical use. There is a need to set the standards for proper identification of the raw drug. So, this study was designed to establish various pharmacognostical standards which can help in ensuring identification of Katuka, a well known herb in Ayurvedic medicine. Botanically, the drug Katuka is Picrorhiza kurroa Royal ex. Benth belonging to the family Scrophulariaceae. Katuka is a valuable bitter tonic and is mainly used in Ayurveda for its hepatoprotective action. Its rhizome is used for medicinal purpose. So, macroscopical and microscopical characters of intact and powdered rhizome were studied. Macroscopic study of rhizome and its powder indicated the organoleptic characters like size, shape, colour, odour, taste and texture. Microscopic study of T.S. of rhizome showed the presence of cork, cortex, vascular cambium, xylem, phloem, pith and pith ray. Microscopic study of powder of rhizome showed the presence of starch grain, cork cells, xylem vessels, and pith cell with pitted wall thickenings, tracheid and lignified fiber. Pharmacognostical characters of rhizome of Katuka revealed from this study will help in standardization of this raw drug and preventing adulteration in the herbal raw drug market.